LEGAL PROTECTION ON FEMALE WORKERS SUBJECT TO HARRASSMENT IN WORK RELATIONS - Tobing, Christina NM (Jurnal Hukum dan Peradilan, 2020)
This study aims to describe the legal protection in the field of labor in Indonesia for female workers who had experienced harassment in work relationships.The research method used is normative juridical through statute approach, conceptual approach and case approach Baiq Nuril. The data source is in the form of primary legal materials, namely the Manpower Act, the PPHI Law, the ITE Law, the Criminal Code, the Human Rights Law and the MA Decision No.  574 K / Pid.Sus / 2018, also secondary legal materials in the form of the PKS Draft Bill, books, papers and journals that contain views and doctrines developed in the science of law.The results of the study showed that the Manpower Act had not yet provided the rights of women workers to protect their morals and decencies, as well as treatment that was in accordance with human dignity and religious values in work relations according to human rights. The status of honorary workers in government agencies became unclear after the enactment of the ASN Law.  The UUK and PPHI Law cannot be applied in the case of honorary worker Baiq Nuril, because it does not include the legal subject of employer government agencies.  The rights of workers detained during criminal proceedings cannot be prosecuted in the Industrial Relations Court as a manifestation of the presumption of innocence principle.  Legal protection for female workers who experience non-verbal sexual harassment is not regulated in the Indonesian Criminal Code or in other criminal laws, so that their human rights cannot be maintained before a criminal court.  The PKS Draft Bill has included non-verbal sexual harassment as a form of protection for women, therefore it needs to be authorized by the Parliament immediately.